Empire on the Seine: the policing of North Africans in Paris, 1925-1975 - Prakash, Amit (Oxford studies in modern European history, 2022)
Why are relations between minorities and the police in France so fraught? Stripping away the myth that this tension is a sudden and recent disruption of its universalist republican tradition brought on by the presence of North African immigrants, Amit Prakash locates the origins of contemporary conflicts in race and empire in France's history. In 'Empire on the Seine,' Prakash argues that the m etropole and the colony dynamically co-developed a policing regime over the course of the 19th and 20th centuries to manage colonial and racial difference